Generation of 560 fs soliton at 10 GHz from optically cross-gain-modulation mode-locked SOA fiber laser - art. no. 61021Y - Chiu, I-Hsiang; Lin, Gong-Ru (My University, 2006)
Optically harmonic mode-locking and femtosecond compression of a semiconductor optical amplifier fiber laser (SOAFL) induced by backward injecting a dark-optical-comb pulse-train at 10 GHz is demonstrated for the first time. The injected dark-optical-comb with 25-ps pulsewidth can be generated by seeding tunable laser into a Mach-Zehnder intensity modulator (MZM) at DC biased point of 0 V. The MZM is driven by a commercial electrical comb generator under an input microwave power of 28 dBm at repetition frequency of 10 GHz. Theoretical simulation indicates that the backward injection of dark-optical-comb results in a wide gain-depletion width (as well as a narrow gain window of <= 25 ps) within one modulation period, providing a cross-gain-modulation mode-locking of the SOAFL with a shortest pulsewidth of 5.4 ps at 10 GHz. The difficulty in mode-locking the SOAFL by an optical short pulse (bright-optical comb) injection is also demonstrated and elucidated by the insufficient gain-depletion time (as well as modulation depth). After propagating through a 75m-long dispersion compensating fiber (DCF), the negatively chirped SOAFL pulsewidth that is mode-locked by the backward injected dark-optical-comb can be linearly dispersion-compensated and slightly shortened to 3.9 ps. By increasing the peak power of the dispersion-compensated SOAFL pulse to 51 W and propagating it through a 76.7m-long single mode fiber (SMF), an eighth-order nonlinearly soliton compression is achieved with the pulsewidth, linewidth, and time-bandwidth product of 560 fs, 4.5 nm and 0.31, respectively.